2022
DOI: 10.1063/5.0091819
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of ions and ionic clusters upon ionization of ethane in helium droplets

Abstract: Helium droplets are unique hosts for isolating diverse molecular ions for infrared spectroscopic experiments. Recently, it was found that electron impact ionization of ethylene clusters embedded in helium droplets produces diverse carbocations containing three and four carbon atoms, indicating effective ion-molecule reactions. In this work, similar experiments are reported but with saturated hydrocarbon precursor, such as ethane. In distinction to ethylene precursors, no characteristic bands of larger covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A previous radiolysis study 69 also suggested the formation of covalently bound adducts of C 2 H 5 + and C 2 H 6 and their decay by loss of H 2 . In contrast, the He droplet study 68 gave only evidence of clusters of the cation fragments with neutral C 2 H 6 . Our study confirms the formation of covalent dimers.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…A previous radiolysis study 69 also suggested the formation of covalently bound adducts of C 2 H 5 + and C 2 H 6 and their decay by loss of H 2 . In contrast, the He droplet study 68 gave only evidence of clusters of the cation fragments with neutral C 2 H 6 . Our study confirms the formation of covalent dimers.…”
Section: Resultsmentioning
confidence: 87%
“…66 Later, the formation of butane from C 2 H 6 was investigated by MS of H 2 gas with an admixture of C 2 H 6 at temperatures between 128 K and 625 K 67 and by infrared spectroscopy of He droplets (0.4 K) doped with C 2 H 6 and irradiated with 100 eV electrons. 68 The former work 67 detected C 4 H 11 + and its decay to C 4 H 9 + and monitored the temperature dependence of the reaction. A previous radiolysis study 69 also suggested the formation of covalently bound adducts of C 2 H 5 + and C 2 H 6 and their decay by loss of H 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations